The Relationship of Parents' Role in Social-Emotional Development with Preschool Children's Learning Concentration - Yuliatil Adawiyah Harahap; Dirayati Sharfina; Bintang Bintara S. Kembaren (Althar Cendikia Education, 2026)
Education plays a fundamental role in shaping children's character and developing their potential. Concentration in learning is a key factor influencing children's ability to absorb information and understand learning materials. Parents who provide limited emotional guidance or have insufficient awareness of their role may negatively affect their children's social-emotional development and learning concentration. This study aimed to examine the relationship between parents' role in social-emotional development and preschool children's learning concentration at MDA Fatimaturridha Medan. A quantitative study with a cross-sectional design was conducted involving 55 parents and preschool children selected through random sampling. Data were collected using questionnaires and analyzed with Fisher's Exact test. The results showed that most parents had a low role in supporting children's social-emotional development (49.0%), while most children had low learning concentration (45.4%). Fisher's Exact test revealed a significant relationship between parents' role and children's learning concentration (p = 0.016). The findings indicate that greater parental involvement in supporting children's social-emotional development is associated with better learning concentration. Strengthening parents' awareness and active participation in creating a supportive emotional and learning environment at home may help improve preschool children's learning concentration.